Molecular and cellular analysis of a novel HBA2 mutation (HBA2: C.94A>G) shows activation of a cryptic splice site and generation of a premature termination codon - Qadah, T.; Finlayson, J.; Joly, P.; Ghassemifar, Reza (2014)
In this study, we describe the clinical features and provide experimental analyses of a novel point mutation affecting the penultimate nucleotide of the first exon of the HBA2 (HBA2: c.94A>G) gene identified in a 26-year-old female who also carries a heterozygous Hb E (HBB: c.79G>A) variant. The aim of the study was to investigate the impact of this point mutation on the transcriptional activity of the HBA2 gene using a combination of an initial in silico prediction followed by in vitro mutagenesis and transcriptional activity assessment. The analyses revealed that the HBA2: c.94A>G point mutation causes the activation of a cryptic splice site located 49bp upstream of the exon1-intron1 boundary in both HBA2 long and short isoforms, thus generating a frameshift and a premature termination codon between codons 48 and 49 in the second exon. A rapid degradation of the aberrantly spliced transcripts by the nonsense mediated decay (NMD) surveillance system is highly indicative of an a-thalassemia (a-thal) phenotype. However, the abnormal mRNA may not be entirely degraded since the proband presents a slight splenomegaly that could be the sign of extra vascular hemolysis. © 2014 Informa Healthcare USA, Inc.